2015
DOI: 10.1016/j.yhbeh.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental exposure of zebrafish (Danio rerio) to 17α-ethinylestradiol affects non-reproductive behavior and fertility as adults, and increases anxiety in unexposed progeny

Abstract: Exposure to estrogenic endocrine disruptors (EDCs) during development affects fertility, reproductive and non-reproductive behavior in mammals and fish. These effects can also be transferred to coming generations. In fish, the effects of developmental EDC exposure on non-reproductive behavior are less well studied. Here, we analyze the effects of 17α-ethinylestradiol (EE2) on anxiety, shoaling behavior and fertility in zebrafish after developmental treatment and remediation in clean water until adulthood. Zebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 78 publications
3
33
1
1
Order By: Relevance
“…In recent studies, we found that low-dose EE 2 exposure of both zebrafish and guppies during development resulted in increased anxiety as adults (Volkova et al, 2012, 2015b), suggesting irreversible changes of the neuroendocrine system. We have also found that the effects on anxiety behavior from developmental exposure of EE 2 was transmitted to the first and the second generation of unexposed progeny in both guppy and zebrafish (Volkova et al, 2015a,b). Effects of EDCs at the level of tissue organization in the developing brain has in mammals been observed to affect fertility and behavior (McLachlan, 2001; Crews and McLachlan, 2006; Dickerson and Gore, 2007).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…In recent studies, we found that low-dose EE 2 exposure of both zebrafish and guppies during development resulted in increased anxiety as adults (Volkova et al, 2012, 2015b), suggesting irreversible changes of the neuroendocrine system. We have also found that the effects on anxiety behavior from developmental exposure of EE 2 was transmitted to the first and the second generation of unexposed progeny in both guppy and zebrafish (Volkova et al, 2015a,b). Effects of EDCs at the level of tissue organization in the developing brain has in mammals been observed to affect fertility and behavior (McLachlan, 2001; Crews and McLachlan, 2006; Dickerson and Gore, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…EE 2 concentrations were analyzed in single or duplicate samples as previously described in Volkova et al (2015b). Briefly, water samples (100 mL) were extracted on 100 mg Strata X-33μ Polymeric Reversed Phase cartridges, reconditioned with MeOH.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 Com relação aos ftalatos, Singh e Li reportaram vinte doenças associadas à exposição a três principais compostos (DnOP, BBP e DEHP), incluindo disfunções no sistema endócrino, genital e uroló-gico, complicações no fígado e doenças cardiovasculares. 139 Outros estudos mostraram que a exposição de diferentes organismos frente aos interferentes endócrinos levaram à ocorrência de efeitos como a feminização de peixes, [140][141][142][143][144][145][146][147][148][149] alterações no desenvolvimento de moluscos e anfíbios, [150][151][152][153][154] disfunções no metabolismo da testosterona em Daphnias 155,156 e o desenvolvimento anormal de órgãos em diferentes organismos aquáticos. 19,146,149,150,157,158 Na Índia, após observarem o declínio de cerca de 95% da quantidade de uma espécie de urubus (Oriental white-backed vulture) na década de 90, Oaks e colaboradores apresentaram fortes evidencias de que as doenças renais que afetaram os animais foram decorrentes da ingestão de resíduos de diclofenaco presentes nas carcaças de búfalos e cabras tratados com o fármaco.…”
Section: Efeitos Relacionados à Presença De Compostos Interferentes Eunclassified
“…19,20 PPs have been detected in surface waters of 41 countries, 21 and it has been found that low-level chronic exposure to PPs can have adverse and sometimes unexpected effects on nontarget organisms. 22,23 Surface water concentrations of iron oxide nanoparticle (IONP) based MRI contrast agents, modelled using 25% and 50% market penetration (i.e., replacement of gadolinium-based MRI contrast agents), were estimated to be 3.1 ng L −1 and 8.4 ng L −1 for the years 2015 and 2020 respectively in Germany. 24 Annual surface water concentrations for select gold nanoparticle-based medical applications were modelled to be 5 and 470 pg L −1 for the US and UK respectively.…”
Section: Introductionmentioning
confidence: 99%